Aquilaria malaccensis polyploids as improved planting materials - A. Rahman, Siti Suhaila; Mohd Saleh, Norihan; Muhammad, Norwati; Mohamad Ali, Nor Azah; Mansor Clyde, Mahani; Namasivayam, Parameswari; Kodi, I. K.; Jamil, Mailina; Azlan, Azrina; Hassan, Nor Hasnida; Ismail, Haliza; Abdullah, Nazirah; et al. (Forest Research Institute Malaysia, 2015)
Aquilaria malaccensis is an agarwood-producing timber species used in many traditional remedies and modern therapeutic treatments and perfume industries. In this study, we aimed to enhance A. malaccensis phytochemical content through in-vitro polyploidisation. Shoot tip and nodal segment from 8-week-old in-vitro A. malaccensis plantlets were treated with different concentrations of colchicine and trifluralin at various exposure times to obtain polyploids. Tetraploid plantlets (10%) was obtained using nodal segment explants treated with 0.1 mM trifluralin at 120 hours. Chemical profiling of diploid and tetraploid samples (leaf, stem and root) was evaluated separately using headspace-solid phase microextraction (HS-SPME) combined with gas chromatograph mass spectrometry (GCMS). Phytochemical content increased in tetraploid, particularly in stem whereby the total phytochemical contents were 43.19% in tetraploid compared with 5.87% in diploid. The HS-SPME-GCMS analyses showed that tetraploid stem contained high levels of sesquiterpenoids found in agarwood oil such as α-eudesmol (18.3%), α-gurjunene (8.61%) and γ-gurjunene (6.22%). On the other hand, aromadendrene (2.49%) and α-humulene (3.38%) were detected in diploid samples. Tetraploid leaf samples were observed to contain α-humulene (3.79%) while diploid only contained (2E) tridecenol (19%). There were no significant differences between diploid and tetraploid in terms of total phytochemical content in root samples. Nevertheless, high sesquiterpenoid content, γ-gurjunene (14.0%), was detected in tetraploid sample while γ-muurolene (2.96%), in diploid. α-Guaiene content was higher in root samples of diploid (6.49%) than tetraploid (1.09%). These results demonstrated that tetraploid plantlets led to higher yield of total phytochemical content and might facilitate production of high quality A. malaccensis clones.